Larotrectinib for paediatric solid tumours harbouring NTRK gene fusions: phase 1 results from a multicentre, open-label, phase 1/2 study - Laetsch, Theodore W; DuBois, Steven G; Mascarenhas, Leo; Turpin, Brian; Federman, Noah; Albert, Catherine M; Nagasubramanian, Ramamoorthy; Davis, Jessica L; Rudzinski, Erin; Feraco, Angela M; Tuch, Brian B; Ebata, Kevin T; et al. (The lancet oncology, 2018)
Gene fusions involving NTRK1, NTRK2, or NTRK3 (TRK fusions) are found in a broad range of paediatric and adult malignancies. Larotrectinib, a highly selective small-molecule inhibitor of the TRK kinases, had shown activity in preclinical models and in adults with tumours harbouring TRK fusions. This study aimed to assess the safety of larotrectinib in paediatric patients. This multicentre, open-label, phase 1/2 study was done at eight sites in the USA and enrolled infants, children, and adolescents aged 1 month to 21 years with locally advanced or metastatic solid tumours or CNS tumours that had relapsed, progressed, or were non-responsive to available therapies regardless of TRK fusion status; had a Karnofsky (≥16 years of age) or Lansky (<16 years of age) performance status score of 50 or more, adequate organ function, and full recovery from the acute toxic effects of all previous anticancer therapy. Following a protocol amendment on Sept 12, 2016, patients with locally advanced infantile fibrosarcoma who would require disfiguring surgery to achieve a complete surgical resection were also eligible. Patients were enrolled to three dose cohorts according to a rolling six design. Larotrectinib was administered orally (capsule or liquid formulation), twice daily, on a continuous 28-day schedule, in increasing doses adjusted for age and bodyweight. The primary endpoint of the phase 1 dose escalation component was the safety of larotrectinib, including dose-limiting toxicity. All patients who received at least one dose of larotrectinib were included in the safety analyses. Reported here are results of the phase 1 dose escalation cohort. Phase 1 follow-up and phase 2 are ongoing. This trial is registered with ClinicalTrials.gov, number NCT02637687. Between Dec 21, 2015, and April 13, 2017, 24 patients (n=17 with tumours harbouring TRK fusions, n=7 without a documented TRK fusion) with a median age of 4·5 years (IQR 1·3–13·3) were enrolled to three dose cohorts: cohorts 1 and 2 were assigned doses on the basis of both age and bodyweight predicted by use of SimCyp modelling to achieve an area under the curve equivalent to the adult doses of 100 mg twice daily (cohort 1) and 150 mg twice daily (cohort 2); and cohort 3 was assigned to receive a dose of 100 mg/m2 twice daily (maximum 100 mg per dose), regardless of age, equating to a maximum of 173% of the recommended adult phase 2 dose. Among enrolled patients harbouring TRK fusion-positive cancers, eight (47%) had infantile fibrosarcoma, seven (41%) had other soft tissue sarcomas, and two (12%) had papillary thyroid cancer. Adverse events were predominantly grade 1 or 2 (occurring in 21 [88%] of 24 patients); the most common larotrectinib-related adverse events of all grades were increased alanine and aspartate aminotransferase (ten [42%] of 24 each), leucopenia (five [21%] of 24), decreased neutrophil count (five [21%] of 24), and vomiting (five [21%] of 24). Grade 3 alanine aminotransferase elevation was the only dose-limiting toxicity and occurred in one patient without a TRK fusion and with progressive disease. No grade 4 or 5 treatment-related adverse events were observed. Two larotrectinib-related serious adverse events were observed: grade 3 nausea and grade 3 ejection fraction decrease during the 28-day follow-up after discontinuing larotrectinib and while on anthracyclines. The maximum tolerated dose was not reached, and 100 mg/m2 (maximum of 100 mg per dose) was established as the recommended phase 2 dose. 14 (93%) of 15 patients with TRK fusion-positive cancers achieved an objective response as per Response Evaluation Criteria In Solid Tumors version 1.1; the remaining patient had tumour regression that did not meet the criteria for objective response. None of the seven patients with TRK fusion-negative cancers had an objective response. The TRK inhibitor larotrectinib was well tolerated in paediatric patients and showed encouraging antitumour activity in all patients with TRK fusion-positive tumours. The recommended phase 2 dose was defined as 100mg/m2 (maximum 100 mg per dose) for infants, children, and adolescents, regardless of age. Loxo Oncology Inc.